Analysis and application: Non-equilibrium condensation of CO2 in supersonic flows and subcritical state serving carbon capture - Zhiheng Wang; Yuanyuan Gao; Zhu Huang; Jianan Chen (Case Studies in Thermal Engineering)
Carbon capture is an important solution to address global warming and has significance for constructing an abundant, clean energy system. This work discusses a potential carbon capture approach with non-equilibrium condensation in subcritical state and supersonic flows. A numerical model is created to describe the complicated physical phenomena in supersonic flows. The mass and heat transfer and thermodynamic properties of CO2 in subcritical state are analyzed, the prediction difference of different models on supersonic flows are quantified, the effects of superheat and TW curve on condensation characteristics are explained, and suggestions are given to improve the carbon capture effect. Compared with the two-phase flow, the single-phase model misestimates the expansion state of system, and the prediction difference between the two models is as high as 15.1 %. The displacement of TW curve has varying degrees of impact on condensation characteristics such as nucleation and Wilson point, and the impact on peak nucleation rate is the most obvious. The inlet superheat is linearly correlated with the outlet liquid fraction and outlet droplet radius. The decrease in inlet superheat weakens the thermal motion of CO2 molecules, thereby weakening the non-equilibrium effect during condensation process.